Concussion Among Children in the United States General Population: Incidence and Risk Factors - Cook, Nathan E.; Iverson, Grant L. (Frontiers in Neurology, 2021)
The objective of this study was to examine the incidence of concussion and risk factors for sustaining concussion among children from the United States general population. This prospective cohort study used data from the Adolescent Brain Cognitive Development (ABCD) Study®. Children were recruited from schools across the US, sampled to reflect the sociodemographic variation of the US population. The current sample includes 11,013 children aged 9 to 10 years old (47.6% girls; 65.5% White) who were prospectively followed for an average of 1 year (mean = 367.9 days, SD = 40.8, range 249–601). The primary outcome was caregiver-reported concussion during a 1 year follow-up period. Logistic regression was used to determine which potential clinical, health history, and behavioral characteristics (assessed at baseline) were prospectively associated with concussion. In the 1 year follow-up period between ages 10 and 11, 1 in 100 children (n = 123, 1.1%) sustained a concussion. In univariate models, three baseline predictors (ADHD, prior concussion, and accident proneness) were significantly associated with sustaining a concussion. In a multivariate model, controlling for all other predictors, only prior concussion remained significantly associated with the occurrence of a concussion during the observation period (Odds Ratio = 5.49, 95% CI: 3.40–8.87). The most robust and only independent prospective predictor of sustaining a concussion was history of a prior concussion. History of concussion is associated with 5.5 times greater odds of sustaining concussion between ages 10 and 11 among children from the general US population.